CONFLICTS AND NATION-BUILDING: THE CASE OF THE NIGER DELTA REGION OF NIGERIA, 1914 – 2010 - Oghi, Felix Ejukonemu (European Scientific Journal, ESJ, 2013)
Nation-Building is a continuous process that have tasked the ability of leaders to handle problems that are crucial to the survival of states. Failure to handle such problems could ultimately lead to disintegration of such states. Conflicts, as part of such problems, are unavoidable in human societies, but there is need to overcome them, or at least, reduce them to the barest minimum regardless of their historical background and political trajectory. The aim of this paper is to arouse the consciousness of leaders in Nigeria and beyond, of the need to address conflict issue adequately and swiftly too, before it plunges states into disintegration. This paper therefore, examines the concept of conflicts as it relate to the Niger Delta region of Nigeria. Among other things, it discusses the Niger Delta situation and the development of armed struggle and stress that some steps should be taken to solve the problem.